2007
DOI: 10.1073/pnas.0611357104
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale fluid/fluid phase separation of proteins and lipids in giant plasma membrane vesicles

Abstract: The membrane raft hypothesis postulates the existence of lipid bilayer membrane heterogeneities, or domains, supposed to be important for cellular function, including lateral sorting, signaling, and trafficking. Characterization of membrane lipid heterogeneities in live cells has been challenging in part because inhomogeneity has not usually been definable by optical microscopy. Model membrane systems, including giant unilamellar vesicles, allow optical fluorescence discrimination of coexisting lipid phase typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

43
854
2
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 755 publications
(911 citation statements)
references
References 64 publications
43
854
2
2
Order By: Relevance
“…Model membrane experiments have shown that liquidordered microdomains in fluid membranes can exist and that proteins can preferentially segregate into the fluid or the ordered phase domain [25,26]. However, biological membranes are much more complex than synthetic membranes, and the presence of lipid rafts in intact cells still remains to be proved.…”
Section: Lipid Microdomains and Membrane Raftsmentioning
confidence: 99%
See 2 more Smart Citations
“…Model membrane experiments have shown that liquidordered microdomains in fluid membranes can exist and that proteins can preferentially segregate into the fluid or the ordered phase domain [25,26]. However, biological membranes are much more complex than synthetic membranes, and the presence of lipid rafts in intact cells still remains to be proved.…”
Section: Lipid Microdomains and Membrane Raftsmentioning
confidence: 99%
“…A consensus definition of membrane rafts emerged from the Keystone Symposium on Lipid Rafts and Cell Function (March [23][24][25][26][27][28]2006): "Membrane rafts are small (10-200nm), heterogeneous, highly dynamic, sterol-and sphingolipid-enriched domains that compartmentalise cellular processes. Small rafts can sometimes be stabilised to form larger platforms through protein-protein and protein-lipid interactions" [41].…”
Section: Lipid Microdomains and Membrane Raftsmentioning
confidence: 99%
See 1 more Smart Citation
“…The best studied examples include Ras, influenza hemagglutinin, and components of the high affinity IgE receptor signaling pathway (Wilson et al 2002;Parton and Hancock 2004;Wilson et al 2004;Hess et al 2005) (Takeda et al 2003). In addition, large-scale lipid phase separation can be observed in plasma membrane blebs (Baumgart et al 2007). Although these approaches have provided valuable information about lipid rafts and related membrane microdomains, their use is limited to fixed or perturbed cells.…”
Section: Methods For Studying Lipid Rafts In Cells and Artificial Memmentioning
confidence: 99%
“…For example, some proteins expected to associate with L o domains on the basis of their association with DRMs in cells show little partitioning when studied in liposomes (Shogomori et al 2005). With the recent development of methods to examine lipid domain segregation in plasma membrane blebs, it should be possible to begin to examine this model in more detail (Baumgart et al 2007;Sengupta et al 2007). …”
Section: Molecular Mechanisms Underlying Raft Formation and Functionmentioning
confidence: 99%